Briefing: Grand Théâtre de Rabat, Morocco – a case study. Issue 3 (14th March 2019) - Watts, Andrew; Kunchev, Ross
Abstract : The Grand Théâtre de Rabat is part of a programme of Moroccan cultural development. Given the large number of glass-fibre-reinforced concrete panels used for the project in different sizes and configurations, an important aspect was to ensure that a single system was implemented with a single fixing detail, serving as a 'universal' connection detail. Basic material tests and static testing of the connections were undertaken before tender to provide an essential proof-of-concept validation for the proposed design and to test the feasibility of both outputs and process, which would then have to be repeated by the appointed fabricator. In addition, the sizes of the main components were required to be understood at an early stage of the project, to minimise the time required for both fabrication and installation.